Estimativa da capacidade de campo em solos por critérios estáticos e dinâmicos - Lobato, Márcio Godofrêdo Rocha (2019)
Quantifying the water available to plants is essential to assist in decision making regarding soil management operations, especially in irrigated soils. One of the parameters to quantify available water is field capacity, which can be estimated at the laboratory by applying a preestablished matric potential to a soil sample, or by parameters of the soil water retention curve, which does not always correspond to the conditions found in the field, since the dynamics of water redistribution in the soil should be considered. For this reason, field capacity should be estimated in situ in an instantaneous profile-type test. It is worth highlighting that this method is laborious and requires a long time, and may be unfeasible under certain conditions. Thus, the use of mathematical models emerges as a quick option with recognized technical viability, based on the hypothesis that the field capacity estimated by models which employ dynamic criteria is similar to that observed in situ because the dynamics of water redistribution in the soil needs to be considered for its estimation. Given the above, this study aimed to compare the field capacity determined in situ with that obtained by static and dynamic criteria in different soil textural classes, namely: loamy sand, sandy clay loam, sandy clay, clay loam and clay. In the experiments conducted, field capacity was estimated in situ in an instantaneous profile-type test. Data analysis was performed using a completely randomized design, with three treatments for field capacity estimation: instantaneous profile-type test, static criteria and dynamic criteria in each soil textural class, with five replicates. Data normality was evaluated by the Anderson- Darling test. Analysis of variance was carried out by F test and Tukey test was used to compare the means. All tests were applied at 5% significance level. There was no significant difference between the estimated moisture content at field capacity (static and dynamic criteria) and that observed in situ for the textural classes loamy sand and sandy clay. For the textural classes sandy clay loam, clay loam and clay, the protocols using dynamic criteria obtained the best performance compared to those using static criterion, not differing statistically from that observed in situ. The evaluation performed between the protocols that used dynamic criteria permitted to observe that, regardless of whether the hydraulic gradient is unitary or measured in situ, these protocols estimate field capacity better in any soil textural class. It was concluded that methods which use data of water drainage in the soil estimated field capacity better. Field capacity obtained by estimation with one matric potential does not correspond to that obtained in situ, because this potential is static and soil hydraulic properties are essentially dynamic.